Rancang Bangun Robot Three wheeled Omnidirectional Dengan Konfigurasi Mikrokontroler Master-Slave - Rochmanto, Raditya Artha; Muslim, M. Aziz; Rif’an, Mochammad (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2020)
Three wheeled omnidirectional robot has been used in industries and academics fields because its ability to move freely and simultaneously both rotation and translation. Free movement in this robot is assisted by omni wheel which consists of wheels and rollers. So, the movement of this robot is a combination of wheel and roller rotation. At present, the task given to the mobile robot is increasingly complex, so it makes microcontroller’s workload heavier. A microcontroller’s workload could be lightened by master-slave configuration to divide the microcontroller’s tasks. The wheel rotating speed control system uses a pid controller to obtain a fast and stable wheel speed response. The PID parameters, kp,ki,kd were obtained by using the hand tuning method. The testing results shown the average error of robot direction is 4,3750 and the direction of the robot’s face changed 5.750.